(untitled) (American Journal of Business Management, Economics and Banking, 2025)
Improving the practice of currency risk management is one of the mandatory conditions for ensuring the effectiveness of foreign exchange transactions of commercial banks. Since, in the context of an increase in the number and volume of transactions in foreign currencies, banks need to pay special attention to such transactions, since financial results are increasingly dependent on fluctuations in exchange rates. The article identifies current problems associated with the management of foreign exchange risks of commercial banks and develops scientific proposals aimed at solving these problems.